Village Fiscal Policies as an Instrument for Poverty Alleviation: An Empirical Study of the Island Regions of North Maluku, Indonesia - Kurnia Ekawaty Harly; Abdul Chalid Ahmad; Jufri Jacob (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the effect of village fiscal capacity and regional macroeconomic dynamics on poverty reduction in North Maluku Province. Research Method: A quantitative approach was applied using panel data regression analysis covering nine regencies/municipalities in North Maluku during 2017–2024. The independent variables include Village Fiscal Transfers, Village Expenditure, Village Literacy, Human Development Index, and Developing Village Index, while the dependent variable is the Poverty Rate. Results and Discussion: The findings show that Village Fiscal Transfers and the Human Development Index have a significant effect on reducing poverty. Meanwhile, Village Expenditure, Village Literacy, and the Developing Village Index do not show significant effects. These results indicate that fiscal capacity and human development are key factors in improving village welfare, particularly in archipelagic regions. Interregional effects also reveal significant variation, where areas with stronger institutional capacity and better fiscal governance tend to experience faster poverty reduction. Implications: The findings suggest that village fiscal policy should be strengthened through improved governance, human development programs, and more effective allocation of village funds. Further research may include institutional quality and spatial inequality variables. Originality: This study contributes by integrating village fiscal variables and regional macroeconomic indicators in analyzing poverty reduction in an archipelagic province.